Impacto das alterações bucais na qualidade de vida de pré-escolares de Belo Horizonte, Brasil - Ana Carolina Scarpelli Rodrigues Botelho (2011)
The aim of the present study was to assess the impact of oral conditions on the quality of life of Brazilian preschoolers and their families and determine the effect of socioeconomic factors and the perceptions of parents/caregivers regarding health as possible determinants of this impact. For such, a population-based cross-sectional study (n=1632) and population-based case-control study (31 cases and 124 controls) were carried out with five-year-old children enrolled in day care centres and preschools in the city of Belo Horizonte, Minas Gerais and their parents/caregivers. The case and control groups were matched for gender, type of school, parents/caregivers age and schooling and monthly household income. The outcome and exposure variables were impact on the quality of life of the child and presence of untreated dental caries, respectively. The clinical examination was performed by a single, previously calibrated examiner, with the determination of dental caries, malocclusion, traumatic dental injury and developmental defects of enamel. The caregivers were asked to fill out a form containing socio-demographic data as well as an oral health-related quality of life (OHRQoL) questionnaire designed for preschoolers (Brazilian version of the Early Childhood Oral Health Impact Scale B-ECOHIS). Univariate and multivariate analyses of the data were performed using the Statistical Package for the Social Sciences (SPSS, version 15.0). The results of the cross-sectional study demonstrated that the following variables had negative repercussions on OHRQoL, as determined by responses on the Child Impact Section of the B-ECOHIS: experience with dental caries (PR=2.18; 95%CI: 1.88-2.52), position of the child among other siblings in the family (PR=1.20; 95%CI: 1.04-1.39), type of preschool/day care centre (PR=1.36; 95%CI: 1.10-1.69), age of parent/caregiver (PR=1.18; 95%CI: 1.04-1.34), monthly household income (PR=1.48; 95%CI: 1.18-1.85) and perception of the childs overall health status (PR=1.26; 95%CI: 1.06-1.51). On the Family Impact Section, a negative impact on quality of life was associated to experience with dental caries (PR=3.40; 95%CI: 2.83-4.08), age of parents/caregivers (PR=1.16; 95%CI: 1.01-1.33) and monthly household income (PR=1.41; 95%CI: 1.16-1.72). The case-control study demonstrated that the prevalence of one or more teeth with untreated dental caries was greater in the case group (71.0%) than the control group (18.5%) (p<0.001). Children with at least one untreated carious lesion had a greater chance of experiencing a negative impact on OHRQoL than those that were free of untreated dental caries (OR=10.73; 95%CI=4.37-26.35). Dental caries constituted the only normative criterion with a negative repercussion on the quality of life of children and their families. Children with at least one carious lesion had a greater chance of experiencing a negative impact on quality of life than those free of caries. Less economically privileged families and those in which the parents/caregivers were younger experienced a greater impact on quality of life. Parents/caregivers perception of their childs overall health status as poor was associated to diminished quality of life among the children.